Analisis Unsur Fisik dan Batin pada Puisi Sajak Malam, Sajak Hujan, Kembalilah, dan Sajak Aku dan Engkau Karya Heri Isnaini - Nida Nur Aulia; Rela Aditi Bahari; Tazqia Nurfauziah Al-Fiyah (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
Poetry is a form of literary expression that contains physical and mental elements that are interrelated in building deeper and more complex meanings. The problem studied in this study is the identification and analysis of the physical and mental elements contained in the poems of Heri Isnaini, which are known for their imaginative power and emotional depth. This research aims to examine how these elements contribute to the formation of the meaning and aesthetics of poetry, as well as how these poems are able to provide an aesthetic experience to the reader through the choice of words and distinctive language styles. The method used in this study is a literature study, with an approach to literary text analysis to understand the elements that form poetry, both in terms of language and the message conveyed. The results of the study show that the physical elements in these poems include the use of diction rich in imagery, metaphorical and personified majas, and rhyme patterns that strengthen emotional and aesthetic nuances in each stanza. Meanwhile, the inner element depicts universal themes, such as longing, loneliness, love, and reflection of life, which are meaningfully expressed through the use of symbols and implied meanings in each line of the poem.